Exporting consumption: Lifestyle migration and energy use - Winkler, Richelle (2020)
This paper examines how international population movements from highly developed to less developed countries spread environmentally-impactful consumption habits around the world. Lifestyle migration, a phenomenon whereby relatively privileged migrants move in search of a more fulfilling life, is increasingly common around the world and serves as an optimal example for studying the spread of unsustainable consumption. We wonder whether lifestyle migrants take high consumption lifestyles typical in their countries of origin to their destination places and whether their presence in destination communities increases consumption among natives as well. This study investigates these relationships based on the case of Costa Rica, a well-established recipient country for lifestyle migration. We analyze 100% sample microdata from the Costa Rican Census 2011 to test relationships between lifestyle migration and consumption of energy-intensive goods using multilevel models that nest consumption at the household level within communities. Our findings suggest that lifestyle migrants not only consume more energy-intensive goods than native Costa Ricans, but that their presence elevates consumption among native neighbors as well. Thus, lifestyle migration may increasingly serve as a mechanism through which unsustainable consumption patterns are transferred from the Global North to the Global South.